2018
DOI: 10.1002/anie.201806917
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an Al≡Al Triple Bond in the Gas‐Phase Na3Al2 Cluster via Double Electronic Transmutation

Abstract: The discovery of homodinuclear multiple bonds composed of Group 13 elements represents one of the most challenging frontiers in modern chemistry. A classical triple bond such as N≡N and HC≡CH contains one σ bond and two π bonds constructed from the p orbitals perpendicular to the σ bond. However, the traditional textbook triple bond between two Al atoms has remained elusive. Here we report an Al≡Al triple bond in the designer Na Al cluster predicted in silico, which was subsequently generated by pulsed arc dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
1
20
1
Order By: Relevance
“…Note that the Al−Al bond is remarkably short and its bond index (2.604) is near to 3, implying its triple‐bond nature. It should be mentioned that a similar Al≡Al triple bond has been realized recently in the gas‐phase Na 3 Al 2 − cluster through double electronic transmutation . Moreover, two C 2 v ‐symmetric planar structures are found to be the isomers A and B of Li 3 Al 2 + , which are higher in energy by 16.603 and 48.186 kcal mol −1 , respectively, than the global minimum.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Note that the Al−Al bond is remarkably short and its bond index (2.604) is near to 3, implying its triple‐bond nature. It should be mentioned that a similar Al≡Al triple bond has been realized recently in the gas‐phase Na 3 Al 2 − cluster through double electronic transmutation . Moreover, two C 2 v ‐symmetric planar structures are found to be the isomers A and B of Li 3 Al 2 + , which are higher in energy by 16.603 and 48.186 kcal mol −1 , respectively, than the global minimum.…”
Section: Resultssupporting
confidence: 60%
“…It should be mentioned that as imilar Al Al triple bond has been realizedr ecently in the gas-phase Na 3 Al 2 À cluster throughd ouble electronic transmutation. [60] Moreover,t wo C 2v -symmetric planar structures are found to be the isomers A and B of Li 3 Al 2 + , which are higher in energy by 16.603a nd 48.186 kcal mol À1 ,r espectively,t han the global minimum. Note that the two Al atoms tend to bind together as an Al 2 unit in all three minimum-energy structures.A lso, it is found that the Li atoms tend to form at riatomic Li 3 subunit in the least favorable structure, B.…”
Section: Group 1( Limg + + )mentioning
confidence: 94%
See 1 more Smart Citation
“…Cotton et.al in 1964, [7,8] more and more complexes containing metal-metal multiple bond have been reported and synthesized since then. [9][10][11] Up to now, the CrÀ Cr five-fold bond still remains the record of the highest bond order among the stable species, [12] although the theoretical bond order of the transition metal diatoms can reach six. [2,[13][14][15] However, not all transition-metal atoms can readily form such high multiple bond [6,[16][17][18] and Zinc is one of them.…”
Section: Introductionmentioning
confidence: 99%
“…The first metal‐metal multiple bonded system of [Re 2 Cl 8 ] 2− was proposed by F. A. Cotton et.al in 1964, more and more complexes containing metal‐metal multiple bond have been reported and synthesized since then . Up to now, the Cr−Cr five‐fold bond still remains the record of the highest bond order among the stable species, although the theoretical bond order of the transition metal diatoms can reach six .…”
Section: Introductionmentioning
confidence: 99%